Who am I kidding? : what project leaders can learn from a stand-up comedian - Jóhanna Jakobsdóttir 1978- (2017)
This study is to call attention to the techniques that stand-up comedians knowingly and systematically apply and how those techniques can be of use to the project leader. A great stand-up comedian utilises certain principles both in writing of material as well as in his/her performance. There is some basis of research on humour and management but surprisingly little has been written about the connection between project management and the art of stand-up. The research question was What can the project leader learn from the stand-up comedian? Inviting Judy Carter, a well-known comedienne, to Iceland, where she set up two leadership workshops in Reykjavik University, as well as hosting an open talk, explored this question. Judy Carter, who has extensive experience in motivational speaking, both for leaders as well as hosting stand-up comedy workshops for comics, introduced some ideas that I hypothesise could be useful for project leaders, such as the art of self-deprecating humour in management, conflict resolution through humour and thinking outside of the box. The experiment was observed in a participatory way; participants gave their feedback at the end of each session and responded to a survey immediately after the workshop. The results gave a convincing indication that stand-up techniques can be a helpful addition to the project manager’s toolbox.